Aktivitas Antibakteri Kitosan dari Tulang Rawan Cumi-Cumi (Loligo sp.) Terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Laode Muhamad Hazairin Nadia; La Ode Huli; Waode Nilda Arifiana Effendy; Frets Jonas Rieuwpassa; Imra Imra; Nurhikma Nurhikma; Eko Cahyono (Universitas Sriwijaya, 2021)
Squid (Loligo sp.) is one of fisheries commodities export in Indonesia. Squid has cartilage that can be utilized in the food and non-food sectors. The inner skin of the squid cartilage contains chemical compounds are chitin and chitosan. The objectives of this research are to produce chitosan from squid cartilage and tested the antibacterial effectiveness of chitosan in bacteria Staphylococcus aureus and Escherichia coli. The research method was carried out in twophase; the manufacturing phase of chitosan from squid cartilage and the testing phase for the antibacterial activity of chitosan. The results of the first phase of this study indicate that the chitosan produced meets the quality standards of chitosan with water content 7.82% (bk), ash content 0.57% (bk), nitrogen content 3.18% (bk) and degree of deacetylation 87.43%. Further more the results obtained in the second phase showed that the higher of chitosan concentration, the greater of inhibition zone in the tested bacteria. The best antibacterial activity was found at 0.8% chitosan concentration, with an inhibition zone of 12.8 ± 0.06 mm in E. coli and 11.1 ± 0.12 mm in S. aureus. At a concentration of 0.8% showed a greater inhibitory value when compared to 70% alcohol.